Study on the Performance and Exhaust Emission of a Diesel Engine Fueled with Waste Cooking Oil and Its Blends (International Journal of Current Engineering and Technology, 2015)
Biodiesel in any form, whether in pure state or in a mix with other components such as diesel fuel is extensively examined to answer some specific questions that are identical in the process of exhaustion of hydrocarbon in the earth (fossil fuels) which really have effect on the environment that is causing climate change and other environmental dreadful conditions. Waste vegetable cooking oil (WCO) which is a by-product of restaurant after the daily activities and collected as the residue of the vegetable oils. This oil has high possibility to use as a mix fuels for operating diesel engines for supply of energy for its optimal performance. The most important intention of the current research is to evaluate the execution of combustion of the oil, its effluents and burning characteristics of biodiesel fuel resulting from using the blend of waste cooking oil mix with normal fuel (diesel) at B10% and B20% (that is 10% of waste cooking oil mix with 90% diesel) base and the volume is then preheated for the fuels to ignite. The evaluation structures that assess the performances which were: brake pedal thermal effectiveness, brake pedal precise energy utilization, energy productivity. The emission structure includes carbon monoxide, carbon dioxide, un-burnt hydrocarbon (shoot), oxides of nitrogen and smoke opacity. These are then measured with diverse fuels mix and weigh against the base line outcome. The diverse characteristics of waste cooking oil subsequent to transesterification were contained by satisfactory boundaries of standards as stipulated by various nations. The brake pedal thermal effectiveness of waste cooking oil methyl ester and its mix with diesel were inferior to diesel and brake pedal precise energy utilization was discovered to be superior. Nevertheless, carbon monoxide, carbon dioxide, hydrocarbons and smolder were discovered to be lower with waste cooking oil biodiesel fuel. NOx emissions on waste cooking oil biodiesel and its mixture were higher than Diesel. The outcome from the research propose that biodiesel resulting from waste cooking may possibly be a superior alternate to diesel fuel in diesel engine in the nearest future and its mixture may perhaps be utilized in a traditional diesel engine devoid of any alteration.
Keywords: Waste cooking oil; Brake thermal efficiency; Exhaust emissions